Correlation between high sensitivity C reactive protein (Hs-CRP) and neutrophil-to-lymphocyte ratio (NLR) with functional capacity in post COVID-19 syndrome patients - Widasari, Nina; Heriansyah, Teuku; Ridwan, Muhammad; Munirwan, Haris; Kurniawan, Ferry D. (Narra J, 2023)
Post coronavirus disease 2019 (COVID-19) syndrome is one of the causes of reduced functional capacity and work productivity, in particular for healthcare workers. The pathophysiology of the post COVID-19 syndrome is related to complex and multisystem inflammatory mechanisms, and cardiopulmonary exercise rehabilitation program is one of the efforts to improve the recovery process for patients with post COVID-19 syndrome. The aim of this study was to determine the correlation between the level of high sensitivity C-reactive protein (Hs-CRP) and neutrophil-to-lymphocyte ratio (NLR) with functional capacity (VO2max) in individuals with post-COVID-19 syndrome who received moderate- and high-intensity supervised cardiopulmonary exercise. A prospective cohort study was conducted at the Integrated Cardiac Rehabilitation Center of Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia. The supervised cardiopulmonary exercise was conducted for six weeks according to the participant's baseline VO2max. Spearman's and Pearson's correlation tests were used to assess the correlations. A total of 30 individuals (19 and 11 had moderate and high intensity exercise, respectively) were involved in this study. At moderate intensity exercise, the average Hs-CRP and NLR were 3.3 mg/L and 1.99, respectively; while at high intensity, the values were 3.8 mg/L and 1.79, respectively. No significant correlation between Hs-CRP level and functional capacity in both moderate-intensity and high intensity groups. In contrast, NLR was negatively correlated with functional capacity (r=-0.545, p=0.016) in moderate intensity exercise group. In conclusion, NLR value was negatively correlated with functional capacity in individuals with post-COVID-19 syndrome after receiving moderate intensity supervised cardiopulmonary exercise program. Therefore, moderate intensity of cardiopulmonary exercise maybe be used as a program to accelerate the recovery for those with post COVID-19 syndrome.